Argumentação em uma sequência de ensino investigativa envolvendo química forense - Santos, Fernanda dos (2020)
The present study aimed to analyze the development of an investigative teaching sequence (SEI), structured around a theme of Forensic Chemistry, verifying the space generated for argumentation and other epistemic practices, in the context of initial teacher training. The analytical focus was on the characterization of the epistemic arguments and practices developed by the research subjects, in the different phases of SEI. Forensic Chemistry can be considered in the planning of teaching sequences that lead students to argue, as it is a theme that has an investigative character. In addition, it has the potential to favour working with scientific concepts combined with debates around social aspects. In the elaboration of the didactic sequence, we consider the fact that investigative activities have been the object of study in Science Education because they provide means for the emergence of epistemic practices, including argumentation, in addition to assisting students in the construction of scientific knowledge. Epistemic practices can be defined as social activities involved in the production, evaluation and communication of knowledge (Kelly, 2005); therefore, examining epistemic practices, from the research perspective, presumes to direct the gaze to the students' discourse when involved in investigative activities. The data from the application of SEI, called “Contributions of Forensic Chemistry in the investigation of firearm crimes”, were obtained through questionnaires and video recordings. The treatment of the data involved transcriptions of the information obtained through the videos, fragmenting them into episodes of interaction, in order to select, for analysis, those that expressed the evolution of the quality of the students' arguments, as well as the epistemic practices established. To analyze the structure of the arguments expressed during the discussions and in the written texts, we used, as an analytical tool, the Toulmin Argument Standard (TAP). For the analysis of epistemic practices, we used a system of categories proposed by Jiménez-Aleixandre (2008), adapted and synthesized by Silva (2015). The results achieved showed the presence of essential elements of the argument pattern proposed by Toulmin (2006), such as data, conclusion and guarantee of inference, in the statements made by the students in the discussions, as well as in their written texts. As for the analysis of epistemic practices, we verified the predominance of practices inserted in the social instance of knowledge production. These results directed our attention to adjustments in the structure of SEI, aiming to enhance its openness to argumentation and other epistemic practices.